Female athlete triad coalition cumulative risk assessment tool: proposed alternative scoring strategies - Koltun, K. J.; Williams, N. I.; De Souza, M. J. (Applied Physiology, Nutrition, and Metabolism, 2020)
We (i) identified alternative scoring strategies for the Female Athlete Triad Coalition cumulative risk assessment (CRA) tool to be utilized when particular risk factors (bone mineral density (BMD), oligomenorrhea/amenorrhea) cannot be determined; (ii) objectively defined dietary restriction for use in the CRA tool; and (iii) explored proxy measures of energy deficiency. This cross-sectional investigation of exercising women (n = 166) utilized an existing database derived from multiple studies designed to assess health, exercise, and menstrual function. Data from the screening/baseline period of each study included: anthropometrics, dual-energy X-ray absorptiometry, disordered eating questionnaires, descriptive data, and proxy measures of energy deficiency (total triiodothyronine (TT3) and ratio of measured-to-predicted resting metabolic rate (mRMR/pRMR)). Substituting delayed menarche for BMD was the best-fit replacement resulting in 15 (9%) participants being categorized in different clearance categories. When menstrual status cannot be assessed, such as during hormonal contraceptive use, low energy availability (EA) determined using self-report and disordered eating questionnaires was the best substitution, resulting in 34 (20%) participants being categorized in different clearance categories. Based on original clearance categorizations, the provisional group had lower TT3 (78.3 ± 2.2 ng/dL; 92.7 ± 2.7 ng/dL) and Harris-Benedict mRMR/pRMR (0.85 ± 0.01; 0.90 ± 0.01) than the full group. Until an updated risk assessment tool is developed, delayed menarche can substitute for low BMD and low EA for oligomenorrhea/amenorrhea. Novelty This investigation addresses previous limitations of the Triad CRA tool. Disordered eating questionnaires can be used to objectively identify dietary restriction for the low EA risk factor. When a risk factor cannot be assessed, delayed menarche can substitute for low BMD and low EA for oligomenorrhea/amenorrhea.